ANALISIS YURIDIS PERTIMBANGAN HAKIM DALAM PERKARA ADOPSI ANAK PENETAPAN NOMOR 164/Pdt.P/2021/PA.Ptk - NIM. A1011201040, IRSYAD ADI FATWA (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT This research was carried out at the Ponrianak Religious Court. The type of research used is a normative research method in the form of a case study using literature study, namely by reading various literature related to child adoption. In the position of the case that will be discussed, it concerns the issue of child adoption cases from prospective adoptive parents, namely Drs. H. Bambang Soepriadi and Dra. Rafikah, M.Si who wants to adopt a child named Naura Rizki Az-Zahra at the Pontianak Religious Court. Submit an application for adoption to obtain legal certainty from the Pontianak Religious Court regarding the validity of the adoption according to the relevant laws.The title of this research is Juridical Analysis of Judges' Considerations in Child Adoption Cases Decree Number 164/Pdt.P/2021/Pa.Ptk, Formulation of the problem